Transition from senior secondary to higher education : a learning environment perspective. - Nair, Chenicheri C. (Curtin University, 1999)
The first purpose of this study was to validate a modified and personalised form of the College and University Classroom Environment Inventory (CUCEI) and then to use this instrument to examine the actual and preferred classroom environment perceptions of students and instructors at the senior secondary and post secondary levels. A third purpose was to examine students' attitude to their courses on three specific scales, namely, Satisfaction, Difficulty and Speed. A sample of 504 students and24 instructors from Canada and the Australian Capital Territory completed the CUCEI. The students also responded to an attitudinal questionnaire. Statistical analysis confirmed the reliability of the CUCEI. The Cronbach alpha reliability figures, using the individual student as the unit of analysis, ranged from 0.73 to 0.93 and from 0.76 to 0.94 for the actual and preferred versions respectively. Good alpha reliability figures were also apparent for instructor versions, ranging from 0.72 to 0.90 for the actual version and from 0.72 to 0.93 for the preferred version. When the two levels were compared, students at the higher level had a less favourable perception of their learning environment. Hardly any difference in perceptions was seen in the learning environment between male and female students. There were significant differences in the perceptions of the classroom environment by mature students. Mature students perceived task orientation and equity more favourably than did younger students. Senior secondary students were generally more satisfied with their science courses than post secondary students. There was no difference in their attitude to the speed of delivery of science courses. The sample of 24 instructors generally perceived their environment more favourably than did their students, however, senior secondary instructors viewed the learning environment more favourably than the instructors at the post secondary level. The study also suggests that instructors at the post secondary level are aware of the changes in students classroom environment and seem to take into account these changes. Qualitative data collected from class observations and student and instructor interviews complemented the quantitative findings of the study.